The comparison of systemic inflammatory response markers and Doppler ultrasound parameters between pregnancies with intrahepatic cholestasis and control cases - Mehmet Obut; Süleyman Cemil Oğlak; Özge Yücal Çelik; Şeyhmus Tunç; Ece Öcal; Zeynep Gedik Özköse; Gökhan Bolluk; Sadun Sucu (Perinatal Medicine Foundation, 2023)
Objective: This study aims to detect a relationship between inflammatory markers, ductus venosus (DV) pulsatility index (PI), middle cerebral artery (MCA) PI, and umbilical artery (UA) systole to diastole ratio (S/D) and PI between pregnancies with intrahepatic cholestasis and control cases. Methods: This prospective study included 82 cases having intrahepatic cholestasis of pregnancy (ICP) and 80 gestational age-matched healthy control cases. The Doppler measurements (DV PI, MCA PI, and UA S/D and PI), inflammatory markers (neutrophil to lymphocyte ratio [NLR], platelet to lymphocyte ratio [PLR], mean platelet volume [MPV], and red blood cell distribution width [RDW]), and fetal and maternal outcomes were compared. Results: Patients with ICP had increased PLR value (p=0.019) and decreased lymphocyte count (p=0.004) compared to control cases. Also, there was a positive correlation between PLR value and the presence of ICP (χ2=5.774, p=0.016). There were no significant differences between ICP and control groups concerning NLR, RDW, MPV, and UA PI values. We found higher UA S/D, and DV PI values and lower MCA PI values in pregnancies with ICP compared to controls (p<0.001, p=0.026, and p=0.003, respectively). Conclusion: In ICP cases, the PLR value was significantly increased than the controls, but the NLR, RDW, MPV, and UA PI values were found to be similar to control cases. The UA S/D, and DV PI values were increased, and MCA PI was significantly decreased in the ICP group compared to healthy pregnancies. However, we could not demonstrate the benefit of Doppler measurements in predicting neonatal outcomes in ICP cases.